Kisspeptin as a Behavioral Hormone - Mills, Edouard G.A.; O'Byrne, Kevin T.; Comninos, Alexander N. (Seminars in Reproductive Medicine, 2019)
Successful reproduction is dependent not only on hormonal endocrine responses but also on suitable partner selection, copulatory acts, as well as associated emotional, behavioral, and cognitive processes many of which are supported by the limbic system. The reproductive hormone kisspeptin (encoded by the KISS1/kiss1 gene) is now recognized as the key orchestrator of the reproductive axis. In addition to the hypothalamus, prominent kisspeptin neuronal populations have been identified throughout limbic and paralimbic brain regions across an assortment of species. In this review, we detail the emerging roles of kisspeptin signaling in the broader aspects of behavioral, emotional, and cognitive control. Recent studies from zebrafish through humans have provided new molecular and neural insights into the complex role of kisspeptin in interpreting olfactory and auditory cues to govern sexual partner preference, in regulating copulatory behaviors and in influencing mood and emotions. Furthermore, emerging roles for kisspeptin in facilitating memory and learning are also discussed. To this end, these findings shed new light onto the importance of kisspeptin signaling, while informing the pharmacological development of kisspeptin as a potential therapeutic strategy for individuals suffering from associated reproductive, emotional, and cognitive disorders.
Keywords: kisspeptin; reproductive behavior; olfaction; mood; cognition